The most common anatomical sites exposing to sports injuries among the students of volleyball course at Mu'tah university (Texas Journal of Medical Science, 2022)
This study aimed at identifying the most common anatomical sites exposing to sports injuries among the students of volleyball course at Mu'tah university as well as the most common types of injuries and the causes leading to sports injuries among the students of volleyball course at Mu'tah university. The study used the descriptive approach and the questionnaire was used as the study instrument for data collection. The study sample consisted of (22) students of those enrolled in the course of volleyball in the faculty of Physical Education at Mu'tah university, who were chosen purposively. (SPSS) was used for analyzing the study results. The results revealed that the most common sports injuries among the students enrolled in the course of volleyball in the faculty of sports sciences at Mu'tah University are related to elbow joints, the most common types of injuries among the students enrolled in the course of volleyball in the faculty of sports sciences at Mu'tah University are cramps and the most common causes leading to injuries among those students are related to fatigue due to the large number of applied lectures given to students. The study recommended the necessity of paying more attention to the sufficient warming up due to its importance in reducing sports injuries.